L’art contemporain au prisme des biotechnologies - Catherine Voison (Amnis)
By using living matter as both a tool and material for their artwork, bio-artists reconfigure nature in vivo and create entirely new live entities in the laboratory. The manipulation and transformation of natural organisms – ranging in size from microscopic to macroscopic – affords artists the chance to establish new relationships between humans and their biotope, and impart greater complexity to the meaning of the word ‘nature’ and its occurrences. Yet live organisms ‘re-natured’ by artists are incarnations of both the best and the worst of all worlds. Found at the fringes of medical and industrial research, biological creations that emerge from the halls of science for exhibition in the art world presage the social and environmental consequences of taking technical control of the natural mechanisms of life.